The Role of Digitalization on Sustainable Development: An Empirical Study of Indonesia - Alfiani Farida; Syafruddin Karimi; Febriandi Prima Putra (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
This study empirically investigates the impact of digitalization on sustainable development achievement in Indonesia. The investigation draws upon secondary data, covering annual data from 34 provinces of Indonesia spanning from 2013 to 2021. Digitalization is proxied by the subindices of the Information and Communication Technology (ICT) Development Index (IP-TIK) published by the Central Statistic Agency (BPS), while the achievements of sustainable development are measured by a composite index employing 19 indicators covering economic, social, and environmental dimensions. Utilizing the System Generalized Method of Moment (SGMM), the results show that the promotion of access to ICT and gross fixed capital income appears to be a way of enhancing sustainable development achievement in the short and long run. Conversely, the increase in ICT usage and foreign direct investment have proved to significantly dampen the sustainable development achievement of Indonesia in the short and long run. Efforts are required to ensure equal access to ICT and to promote the utilization of ICT for productive purposes. Furthermore, strategies to attract foreign capital inflow should be paired with the reinforcement of sectoral and environmental regulations to address the adverse effects of foreign investment.